Probiotic Sheep Milk Ice Cream with Inulin and Apple Fiber - Magdalena Kowalczyk; Agata Znamirowska; Magdalena Buniowska (Foods, 2021)
The aim of the study was to assess the effect of the addition of inulin and the replacement of part of the inulin with apple fiber on the physicochemical and organoleptic properties of ice cream. Moreover, the survival of Bifidobacterium animalis ssp. Lactis Bb-12 and Lactobacillus rhamnosus was studied in sheep milk ice cream. There was no effect of the apple fiber and the type of bacteria on the number of bacteria in the probiotics after fermentation. As a result of freezing, in the mixture containing Bifidobacterium animalis ssp. Lactis Bb-12, there was a significant reduction in the bacteria from 0.39 log cfu g−1 to 0.46 log cfu g−1. In all of the ice cream on the 21st day of storage, it exceeded 10 log cfu g−1, which means that the ice cream retained the status of a probiotic product. The Lactobacillus rhamnosus ice cream showed a lower yellow color compared to the Bifidobacterium Bb-12 ice cream. The overrun of the sheep’s milk ice cream was within the range of 78.50% to 80.41%. The appearance of the sheep’s milk ice cream is influenced significantly by the addition of fiber and the type of bacteria and the interaction between the type of bacteria and the addition of fiber, and storage time and fiber.